Laparoscopic Extraperitoneal Simple Prostatectomyfor Benign Prostate Hyperplasia:A Two-Year Experience - Bulent Oktay; Gokhan Koc; Hakan Vuruskan; Mahmut Esad Danisoglu; Yakup Kordan (Urology Journal, 2011)
PURPOSE: To evaluate the feasibility of laparoscopic simple prostatectomyfor large volume prostates.MATERIALS AND METHODS: Between October 2007 and July 2009, laparoscopicsimple prostatectomy was performed on 16 patients with the prostates over 80mL. All the patients were operated with transvesical method. Peri-operativeand 3rd postoperative month data were recorded and evaluated.RESULTS: The mean prostate volume was 147 mL (range, 80 to 200 mL). Themean operation time, blood loss, duration of hospitalization, and duration ofdrain placement was 133 minutes (range, 75 to 210 minutes), 134 cc (range,50 to 300 cc), 3.9 days (range, 2 to 7 days), and 2.1 days (range, 2 to 3 days),respectively. Only one patient required blood transfusion due to postoperativebleeding and clot obstruction in the catheter lumen. Postoperative infectionwas not seen and recatheterization was not needed in any of the patients.All the patients’ pathology reports were noted as benign. Pre-operative andpostoperative International Prostate Symptom Score were 9.2 and 25.4,respectively. Maximum urinary flow rate was 4.0 mL/sec pre-operatively,but 24.7 mL/sec postoperatively.CONCLUSION: Laparoscopic simple prostatectomy is a feasible method withlow morbidity and improved postoperative outcomes.